Analisis Kesesuaian Wilayah Untuk Budidaya Ikan Keramba Jaring Apung di Perairan Girsang Sipangan Bolon Danau Toba (Analysis of suitability area for floating net cage ini Lake Toba Girsang Sipangan Bolon) - Khairunnisa Khairunnisa; Ternala Alexander Barus; Zulham Apandy Harahap (AQUACOASTMARINE, 2014)
Toba Lake is a lake that is used as aquaculture land. Floating net cage activities in the Toba Lake has been done by the public since 1986, but the rapid development of floating net cage occurred since 1998 through the intensive cultivation net high fish density. This study aims to analyze potential areas for floating net cage ini Toba Lake Girsang Sipangan Bolon, Simalungun by the suitability matrix method. This research use the scorring method/weighting. Determination of weighting and scoring is done to put a value on criteria that support the aquaculture activities by linking the chemical physical parameters. These parameters include temperature, DO, pH, brightness, current, depth, BOD, and ammonia. The results showed that the suitability grade in Toba Lake Girsang Sipangan Bolon is very suitable and suitable class. This shows that Toba Lake Girsang Sipangan Bolon is a potential area for floating net cage.Keyword : Toba Lake, Floating Net Cage, Suitability Index